Repetitive Transcranial Magnetic Stimulation to Maintain Treatment Response to Electroconvulsive Therapy in Depression: A Case Series - Noda, Yoshihiro; Daskalakis, Zafiris J.; Ramos, Cinthia; Blumberger, Daniel M. (Frontiers in Psychiatry, 2013)
Electroconvulsive therapy (ECT) is the most effective treatment for a refractory major depression in the context of both unipolar and bipolar affective disorders. However, the relapse rate within the first 6 months after a successful course of ECT to treat a depressive episode can be as high 50%. Evidence-based strategies to prevent relapse have partial efficacy and are associated with problematic adverse effects limiting their use as long-term treatments. Repetitive transcranial magnetic stimulation (rTMS) has demonstrated efficacy in treatment-resistant depression (TRD) with a favorable adverse effect profile. Herein, we describe six patients, 4 with unipolar and 2 with bipolar depression, where rTMS was used to maintain response after a successful course of acute and continuation ECT. rTMS was administered once or twice weekly, at 120% of the resting motor threshold. Patients received sequential bilateral rTMS (low frequency right: 600 pulses, then high frequency left: 3000 pulses). The site of stimulation was 6 cm anterior and 1 cm lateral from the site of maximum stimulation of the abductor pollicis brevis muscle. Depressive symptoms were monitored with the quick inventory of depressive symptoms – self rated (QIDS-SR). Five of the 6 patients were able to maintain their response status from from 6 to 13 months at the time of last observation. The use of rTMS may be an important relapse prevention strategy following an acute course of ECT. Controlled studies comparing rTMS to current evidence-based relapse prevention strategies are warranted.